UJI EFEKTIVITAS EKSTRAK BUAH TERONG BELANDA (Solanum betaceum Cav.) TERHADAP PERTUMBUHAN Trichophyton rubrum SECARA in vitro - Dandi Tri Dirgantara (2021)
Trichophyton rubrum is the most common cause of dermatophytosis. The use of synthetic-antifungals has several side effects and resistance. Exract of Tamarillo (Solanum betaceum Cav.) fruits contains active compounds that have potential as antifungal, including alkaloids, saponins, tannins, phenolics, and flavonoids This study aims to determine the effectiveness of tamarillo extract as antifungals against the growth of T. rubrum. This study used tamarillo with concentration of 20%;-40%;-60%; and 80%, ketoconazole as positive control, and aquadest as negative control. The antifungal test was conducted by using well diffusion method on Saboraud-Dextrose-Agar medium and was incubated for 24 hours, 48 hours and 72 hours. Data were analyzed by Kruskall-Wallis-test with the results p=0.01, p=0.000, p=0.000 respectively according to the length of incubation time. Data were analyzed for Post-Hoc by Mann-Whitney-test showing the three groups of data had significant differences in results between the two treatment groups. Most effective extract group was the extract with concentration of 20% at incubation time of 24 hours with relatively strong antifungal properties. The result showed that tamarillo extract is effective as antifungals against the growth of T. rubrum.